A Comparative Study on the Urinary System of the African Giant Rat (Cricetomys Gambianus Waterhouse) and the Wistar Rat - Onyeanusi, B.I.; Adeniyi, A.A.; Ayo, J.O.; Ibe, C.S.; Onyeanusi, C.G. (Pakistan Journal of Nutrition, 2009)
A comparative study was carried out on the urinary system of the African Giant Rat (AGR) and the Wistar Rat (WR) using standard laboratory procedures. The mean liveweight of the AGR and WR were 863.590±33.740 and 140.625±6.078 g, respectively. The mean kidney weight of the male and female AGR and WR were 2.119±0.062, 2.053±0.009, 0.633±0.091 and 0.572±0.132 g, respectively. It was observed that the mean kidney weight in the male was higher than that of the female in both AGR and WR but the difference was not significant (p>0.05). The mean weight of the right kidney was heavier than that of the left kidney in both the AGR and WR. The mean weight of the right kidney of the AGR was 2.21±0.051 g while, the left was 2.00±0.055 g. The mean weight of the right kidney in the WR was 0.633±0.012 g while, the left was 0.596±0.022 g. No significant difference (p>0.05) was obtained in the thickness of the bladder and its length in both AGR and WR but there was a high significant difference (p<0.001) between the ureter length of the AGR and the WR. The length of the right ureter was longer than the left and the female had a slightly longer ureter than the male in both rats. The relative thickness of the medulla, which is an indicator of the length of the loop of Henle, was 4.297 in the AGR while, that of the WR was 5.6. The higher relative thickness of the medulla (5.6) signifies that the kidney of the WR has an anatomical adaptation for the concentration of urine and thus, better conservation of water in the arid zone while, the lower relative thickness of the medulla (4.2) of the AGR suggests lack of appropriate anatomical adaptation in the kidney for conservation of water. The study has also provided a baseline morphometric data on the urinary system of both the AGR and WR in the Northern Guinea Savannah zone of Nigeria.